Misconceptions in the Sinhala Buddhist-Muslim Conflict in Sri Lanka: A New Perspective on ethnic conflict in post-colonial era - Mahroof, Sithy Rifa; Razick, Ahamed Sarjoon (UIN Sunan Kalijaga Yogyakarta, 2023)
Sri Lanka's vibrant diversity, encompassing a wealth of ethnicities and religions, is tragically fractured by the ongoing conflict between the dominant Sinhala Buddhist majority and the marginalized Muslim minority. This study traces the origins of the conflict between Sri Lanka's dominant Sinhala Buddhist majority and the marginalized Muslim minority back to the colonial legacy that imposed a dichotomous societal structure. Employing a qualitative approach with the Self and the Other framework, this research utilizes the iceberg model to delve deeper into the underlying causes of conflict. The research reveals that the conflict between Sinhalese Buddhists and the Muslim community arises from an ambiguous sense of self-identity, which is defined by contrasting with the Other. Sinhala Buddhists perceive the growing Muslim community as a threat to the indigenous culture and religion, as reflected in Sinhala culture. This perception is shaped by mental models constructed since the colonial period, during which ethnic and religious classifications were implanted by colonizers as the basis for political rights. The resulting classification fostered a sense of nationalism among the Sinhala Buddhists, fueling resistance against colonial rule. However, this classification also perpetuated a pattern of oppression towards minority groups, viewing them through the same lens as the colonizers viewed the indigenous population, thus perpetuating cycles of conflict and marginalization.